The Discovery of Cytokinin Receptors and Biosynthesis of Cytokinins: A True Story - Romanov, G.A.
The year 2001 saw an amazing progress in cytokinin studies. Ten years ago, cytokinin receptor genes and genes encoding cytokinin biosynthetic enzymes together with the corresponding proteins were identified in plants. These studies elucidated the molecular mechanism of cytokinin effects on the expression of cytokinin responsive genes and ultimately established the endogenous synthesis of cytokinins in plant cells, justifying their membership among plant hormones. The paper describes in short the edifying and sometimes paradoxical story of these fundamental and captivating discoveries.
Keywords: PLANT; CYTOKININ; RECEPTOR; HISTIDINE KINASE; SIGNAL TRANSDUCTION; PRIMARY RESPONSE GENE; CONTROL OF GENE EXPRESSION; CYTOKININ BIOSYNTHESIS